Dynamics of peer assisted learning and teaching at an entrepreneurial university : an experience to share. - Naila Aaijaz; Mohamed Dahlan Ibrahim (2011)
The process of Peer Assisted Learning (PAL) is a situation in which "people from similar social groupings who are not professional teachers help each other to learn and learn themselves by teaching. It is this reciprocity of learning among other things that makes PAL such an attractive idea to educationists. One mission of the FKP (in Malay language - Fakulti Keusahawanan dan Perniagaan) i.e. Faculty of Entrepreneurship and Business at University Malaysia Kelantan is to teach a curriculum developed on the model of “Continuous or Lifelong Learning Process” and “Learning Outcomes” (LO) for students with the help of novel processes like PAL, Collaborative Learning, PBL (Problem Based Learning) etc. We prepare our undergraduate students for successful transition into the entrepreneurial world. For this reason, most of our teaching experience at the University has been focused in this area. Noteworthy researches done in this area are - Jean Piaget (1896-1980), a Swiss psychologist, whose cognitive development theories have been widely discussed in both psychology and educational fields, identified that students must be active agents in creation of their own knowledge. Lev Vygotsky, a Russian psychologist, was interested in applying Marxist social theory to individual psychology (1978). Vygotsky’s research also differentiated between our higher and lower mental functions conceiving our lower or elementary mental functions to be those functions that are genetically inherited, our natural mental abilities. In contrast, he saw our higher mental functions as developing through social interaction, being socially or culturally mediated (Wertsch, 1991:18)